Tipologi Pemimpin dalam Pendidikan Islam - Mukhlis (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2016)
Study of leadership in Islam, the term used is the word caliph, imam, ulil amr and al - mulk. Understanding of each term refers to a person's ability to position itself as a leader (leader) and leadership (leadership). Big and heavy duties of a leader, it is required to it a requirement that the complex and comprehensive, covering three main requirements; (1) the physical requirements, (2) mental spiritual requirements, and (3) the terms of expertise and capabilities. Characters who have demonstrated leadership and success, and this success that needs to be used as a role model is the character of the leadership of the Prophets and Messengers, namely; Siddiq, trust, fathanah and sermons. Four characters of this leadership needs to be developed along with the times and time.